The Efficiency of Multimedia Programs in The Process of Teaching Foreign Languages - Novik Kseniya Pavlovna (Genius Publishing Group, 2022)
The article deals with the application of multimedia technologies in the process of teaching foreign languages, their influence on the formation of communicative competencies (reading, listening, speaking, writing), on the development of critical, figurative, abstract thinking of students. The intensity of learning with the help of multimedia and their effectiveness are proved. The connection between the possibilities of multimedia and the theory of multiple intelligences, the criteria of which correspond to the linguistic, musical, logical-mathematical, spatial, bodily-kinesthetic, intra-personal and interpersonal abilities of a person, as well as the connection between the grammar of foreign languages and the development of human thinking, is considered.
Keywords: multimedia technologies; teaching foreign languages; communicative competencies; critical